Effects of processing on physical properties of extruded snacks with blends of sour cassava starch and flaxseed flour - Mesquita, Camila De Barros [UNESP]; Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2013)
The opportunity to supplement common cassava biscuits with a product of higher nutritional value meets consumer expectations. In this work it was studied the effects of process parameters and flaxseed addition on physical properties of expanded snacks. Extrusion process was carried out using a single screw extruder in a factorial central composite rotatable design with four factors: flaxseed flour percentage (0-20%), moisture (12-20%), extrusion temperature (90-130 °C) and screw speed (190-270). The effect of extrusion variables was investigated in terms of expansion index, specific volume, water absorption index, water solubility index, color parameters (L*, a* ,b*) and hardness. The data analysis showed that variable parameters of the extrusion process and flaxseed flour affected physical properties of puffed snacks. Among the experimental conditions used in the present study, expanded snack products with good physical properties can be obtained under the conditions of 10% flaxseed flour, 230 rpm screw speed, temperature of 90 °C and moisture of 12%.
Keywords: extrusion; physical properties; starch; Linum usitatissimum L